1989
DOI: 10.1021/j100360a029
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of water with sodium bis(2-ethyl-1-hexyl) sulfosuccinate in reversed micelles

Abstract: The hydration of sodium bis(2-ethyl-l-hexyl) sulfosuccinate (AOT) reversed micelles has been studied by three independent methods: differential scanning calorimetry, ESR spin labeling, and 2H NMR. A consistent picture is evolving although the actual hydration numbers differ from method to method. This difference is most likely due to differences in the principles underlying these methods. From both calorimetry and 2H NMR it is concluded that two water molecules are tightly bound to one AOT-Na+ molecule whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
175
1
4

Year Published

1994
1994
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(186 citation statements)
references
References 6 publications
6
175
1
4
Order By: Relevance
“…5,22,23,44,86 Several authors have even found evidence that up to a few water molecules per headgroup are "trapped" at the interface. 23,48 There is a large body of evidence that water mobility, both translational 10,21,65,66 and rotational, 11,49 is greatly reduced inside reverse micelles but increases greatly with micelle size. These trends may be fit by models that assume reduced mobility of interfacial water, 21,48,98 but so far the experiments cannot spatially resolve the mobility.…”
Section: Comparisons With Experimentmentioning
confidence: 99%
See 1 more Smart Citation
“…5,22,23,44,86 Several authors have even found evidence that up to a few water molecules per headgroup are "trapped" at the interface. 23,48 There is a large body of evidence that water mobility, both translational 10,21,65,66 and rotational, 11,49 is greatly reduced inside reverse micelles but increases greatly with micelle size. These trends may be fit by models that assume reduced mobility of interfacial water, 21,48,98 but so far the experiments cannot spatially resolve the mobility.…”
Section: Comparisons With Experimentmentioning
confidence: 99%
“…5 Experimental techniques that have been used to characterize the AOT reverse micelles include light scattering, 41,42 photon correlation, 12 IR spectroscopy, 23,[43][44][45][46][47] NMR, 11,22,[48][49][50][51][52] probe fluorescence, 10,21,53-61 calorimetry, 62,63 small-angle neutron scattering (SANS), 13,14,64 and quasi-elastic neutron scattering. 65,66 While many of these techniques provide information about the structure and properties of reverse micelles, a fundamental dispute remains about the structure of water in the micellar interior.…”
Section: Introductionmentioning
confidence: 99%
“…The list includes fluorescence, 3,4 NMR, [5][6][7] neutron and x-ray scattering, [8][9][10][11] quasi-elastic light scattering, and infrared 12,13 and terahertz 14 spectroscopies, to cite a few relevant examples. On the other hand, and from a theoretical perspective, these systems have also been investigated, normally resorting on computer simulations incorporating different degrees of molecular detail to model the polar and non-polar phases and the surfactants as well.…”
Section: Introductionmentioning
confidence: 99%
“…7 Therefore, size effects on chemical and physical properties in nanometer dimensions can be studied by the use of reverse AOT micelles. Indeed, reverse AOT micelles have been studied by various techniques such as fluorescence spectroscopy 7-21 , NMR 22,23 , ESR 24,25 , , and so on. [29][30][31][32] These studies demonstrated that polarity 8-10 , viscosity 11 , pH 12 , and other properties 30,32 of the water pool in the micelles were different from those in the bulk state and were dependent on the w 0 value.…”
mentioning
confidence: 99%
“…As one of the several advantages of a reverse AOT micellar system, the size of the water pool can be controlled precisely at the nanometer level through the molar ratio of water to AOT: 7 Therefore, size effects on chemical and physical properties in nanometer dimensions can be studied by the use of reverse AOT micelles. Indeed, reverse AOT micelles have been studied by various techniques such as fluorescence spectroscopy [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] , NMR 22,23 , ESR 24,25 , IR [26][27][28] , and so on. [29][30][31][32] These studies demonstrated that polarity [8][9][10] , viscosity 11 , pH 12 , and other properties 30,32 of the water pool in the micelles were different from those in the bulk state and were dependent on the w 0 value.…”
mentioning
confidence: 99%